The Relational Self-Schema Measure: Assessing Psychological Needs in Multiple Self-with-Other Representations. Issue 1 (2nd January 2022) - Scott, Walter D.; Penningroth, Suzanna L.; Paup, Stephen; Li, Xingzi; Adams, Delaney; Mallory, Blake
Abstract: Modern self-schema theory posits multiple representations in memory of the self, with each individual self-schema possessing associative connections to relational contexts (i.e., self-with-other). However, existing self-schema measures typically assess a generalized self unmoored from context. In two studies, we present a new instrument—the Relational Self-Schema Measure (RSSM)—designed to represent the self-schema construct with greater content validity. In Study 1, 512 adults completed an initial version of the RSSM that was subjected to exploratory factor analyses. Support emerged for a reduced four-factor model that included relatedness satisfaction, control satisfaction, self-esteem/status frustration, and autonomy frustration psychological need themes. In Study 2, 516 adults completed a revised RSSM along with measures of self-esteem, attachment, and mood and anxiety symptoms. A separate sample of 191 college students completed the revised RSSM and a measure of dysfunctional attitudes. Confirmatory factor analyses supported the same four-factor model. Moreover, the RSSM exhibited good convergent and discriminant validity as well as incremental validity in predicting positive affect, distress, and anxiety symptoms. Finally, significant within-person variability was apparent across relational schemata that accounted for additional variance in positive affect, distress, and anxiety symptoms.